A robust soft sensor based on artificial neural network for monitoring microbial lipid fermentation processes using Yarrowia lipolytica. Issue 4 (23rd December 2022) - Wang, Kaifeng; Zhao, Wenyang; Lin, Lu; Wang, Tianjing; Wei, Ping; Ledesma‐Amaro, Rodrigo; Zhang, Ai‐Hui; Ji, Xiao‐Jun
Abstract: Microbial oils produced by Yarrowia lipolytica offer an environmentally friendly and sustainable alternative to petroleum as well as traditional lipids from animals and plants. The accurate measurement of fermentation parameters, including the substrate concentration, dry cell weight, and lipid accumulation, is the foundation of process control, which is indispensable for industrial lipid production. However, it remains a great challenge to measure the complex parameters online during the lipid fermentation process, which is nonlinear, multivariate, and characterized by strong coupling. As a type of AI technology, the artificial neural network model is a powerful tool for handling extremely complex problems, and it can be employed to develop a soft sensor to monitor the microbial lipid fermentation process of Y. lipolytica . In this study, we first analyzed and emphasized the volume of sodium hydroxide and dissolved oxygen concentration as central parameters of the fermentation process. Then, a soft sensor based on a four‐input artificial neural network model was developed, in which the input variables were fermentation time, dissolved oxygen concentration, initial glucose concentration, and additional volume of sodium hydroxide. This provides the possibility of online monitoring of dry cell weight, glucose concentration, and lipid production with high accuracy, which can be extended to similar fermentation processes characterized by the addition of bases or acids, as well as changes of the dissolved oxygen concentration. Abstract : A robust soft sensor based on artificial neural network was developed for online monitoring of dry cell weight, glucose concentration, and lipid production with high accuracy in the oleaginous yeast Yarrowia lipolytica, where the input variables were fermentation time, dissolved oxygen concentration, initial glucose concentration, and additional volume of NaOH.